Combined assessment of WT1 and BAALC gene expression at diagnosis may improve leukemia-free survival prediction in patients with myelodysplastic syndromes. Issue 8 (August 2015) - Minetto, Paola; Guolo, Fabio; Clavio, Marino; De Astis, Enrico; Colombo, Nicoletta; Grasso, Raffaella; Fugazza, Giuseppina; Sessarego, Mario; Lemoli, Roberto Massimo; Gobbi, Marco; Miglino, Maurizio
Highlights We analyzed WT1 and BAALC expression levels in MDS patients and diagnosis. WT1 and BAALC combined assessment independently correlated with LFS duration. Molecular evaluation could further improve IPSS and R-IPSS stratification. Adding molecular data to standard prognostic score may help therapeutic choices.